Heat flux classification of CMIP5 model results using self-organizing maps - Jacobi, Christoph; Mewes, Daniel (Universität Leipzig, 2019)
We used the self-organizing maps (SOMs) method on eight models that participated in the Coupled model intercomparison project phase 5 (CMIP5) and two different greenhouse gases (GHG) concentration experiments. The SOMs were created from the winter 500 hPa horizontal temperature flux for each model. The clustering by the SOM revealed that in addition to the three flux pathways found in reanalyses (Pacific, Atlantic and Siberian/continental pathway), superpositions of these occur for the free running climate models, which develop their dynamic more freely than the reanalyses. It was found that the general structure of fluxes is indirectly dependent on the GHG concentrations, as the derived results from SOM patterns are different between the two GHG concentrations. It is suggested that flux patterns change from stable cyclonic motion over the north pole to flux pathways that feature more meridional fluxes through the North Atlantic and North Pacific into the Arctic. Die Methode der Self-Organizing Maps (SOMs) wurde auf acht CMIP5-Modelle mit jeweils zwei verschiedenen Treibhausgasszenarien angwendet. Die SOMs wurden für jedes Modell und jede der beiden Modelläufe für den horizontalen Temperaturfluss in 500 hPa im Winter erstellt. Zusätzlich zu den aus der Analyse von Reanalyse-Daten erwarteten drei Transportwegen (pazifisch, atlantisch und sibirisch/kontinental) wurden Überlagerungen dieser gefunden. Es konnte gezeigt werden, dass die grundsätzliche Struktur der Transporte indirekt abhängig von der Treibhausgaskonzentration ist. Die Ergebnisse deuten darauf hin, dass sich die generelle Struktur des atmosphärischen Transports von einer stabilen zyklonalen Bewegung über dem Nordpol sich zu Transporten verschiebt, welche meridionale Transporte über den Nortdatlantik und den Nordpazifik in die Arktis führen.